Pembelajaran Matematika Modern: Teknologi Gamifikasi dan RME dalam Mengasah Kemampuan Pemecahan Masalah - Rahmi Hayati; Yessi Kartika; Marzuki Marzuki; Asrul Karim; Fachrurazi Fachrurazi (Departement of Mathematics Education, 2025)
This research aims to develop and analyze the effectiveness of applying gamification technology integrated with the Realistic Mathematics Education (RME) approach in mathematics learning to hone students' problem solving abilities. This approach utilizes game elements such as points, levels and challenges combined with the local cultural context as a basis for learning. The research was conducted using qualitative methods, involving teachers and students as the main subjects, with data collected through observation, interviews and analysis of learning documents. The research results show that the integration of gamification technology with RME can significantly increase student learning motivation. Gamification elements create a more interesting and competitive learning atmosphere, while the local culture-based RME approach helps students understand mathematical concepts more concretely and relevant to everyday life. In addition, students' ability to solve problems increases, shown by their success in identifying problems, formulating strategies, and evaluating solutions. Teachers also responded positively to this approach, despite facing challenges such as limited planning time and technological facilities. This research makes an important contribution to modern mathematics learning innovations that are relevant to the needs of the 21st century. The integration of gamification and RME technologies offers great potential to holistically increase students' motivation, understanding and problem-solving skills.